2007
DOI: 10.1016/j.jtcvs.2007.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic carcinoma of the lung: A surgical outcome

Abstract: Pulmonary pleomorphic carcinoma, which often presented in symptomatic male smokers as a large peripheral lesion, carried a poor prognosis, even when early-stage disease was diagnosed and resected. Distant metastases occurred more frequently and earlier, and the survival after relapse was very short, suggesting that this entity should be considered to have a tremendously aggressive malignant behavior. Further investigation of biologic features of pulmonary pleomorphic carcinoma and therapeutic response is a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 11 publications
10
89
2
1
Order By: Relevance
“…Since its pathological definition became widely recognized, pleomorphic carcinoma has been diagnosed more frequently: in our study, its frequency was 0.90% (22/2447 cases). In another recent study, it was found to be 1.6% (45/2743) of resected non-small cell lung cancer (NSCLC) [8]. As in previous reports [8][9][10][11][12], most cases in our study were male with a history of smoking; they exhibited symptoms such as hemoptysis and cough.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since its pathological definition became widely recognized, pleomorphic carcinoma has been diagnosed more frequently: in our study, its frequency was 0.90% (22/2447 cases). In another recent study, it was found to be 1.6% (45/2743) of resected non-small cell lung cancer (NSCLC) [8]. As in previous reports [8][9][10][11][12], most cases in our study were male with a history of smoking; they exhibited symptoms such as hemoptysis and cough.…”
Section: Discussionsupporting
confidence: 75%
“…Recurrence after surgery was frequently observed, and it should be noted that five cases with pN0 disease also relapsed. While Raveglia et al reported that nodal involvement was a determinant prognostic variable of pleomorphic carcinoma of the lung [9], Yuki et al commented that even patients with pN0 disease frequently experienced vascular invasion (57.1%) [8]. We have to keep in mind that pleomorphic carcinoma of the lung has the potential to recur even if the primary lesion is resected at an early stage.…”
Section: Discussionmentioning
confidence: 93%
“…As reported previously, pulmonary pleomorphic carcinoma is prone to invasion of the chest wall and mediastinal tissues, 8 and the incidence in our patients was slightly lower than that previously reported. As reported by Ito et al, 4 because the biological behavior of pulmonary pleomorphic carcinoma is highly malignant and even an early tumor may invade the blood vessels, an early pulmonary pleomorphic carcinoma without lymphatic metastasis may recur or metastasize.…”
Section: Discussionsupporting
confidence: 49%
“…According to several published reports of relatively large patient samples, the five‐year OS rate of patients with PC of the lung after surgery is < 40% 6, 11, 12. Yuki et al .…”
Section: Discussionmentioning
confidence: 99%